Identification and metabolomic characterization of potent anti-MRSA phloroglucinol derivatives from Dryopteris crassirhizoma Nakai (Polypodiaceae) - Bhowmick, Sumana; Beckmann, Manfred; Shen, Jianying; Mur, Luis A. J. (Frontiers in Pharmacology, 2022)
Abstract: Traditional Chinese Medicine (TCM) has been used to treat infectious diseases and could offer potential drug leads. This study evaluates the in vitro antimicrobial activities commercially sourced Dryopteris crassirhizoma Nakai whose authenticity was confirmed by DNA barcoding based on the ribulose bisphosphate carboxylase (rbcL) gene. Powdered rhizomes were sequentially extracted using n-hexane, dichloromethane, ethyl acetate and methanol at ambient temperature. The dried extracts at different concentrations were tested for antimicrobial activities against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus (MRSA), and Mycobacterium smegmatis. D. crassirhizoma extracts exhibited significant antimicrobial activities only against MRSA. Activity-led fractionations of D. crassirhizoma and characterisation by Ultra performance liquid chromatography - tandem mass spectrometry (UPLC-MS/MS) identified two potent anti-MRSA phloroglucinol derivatives: Norflavaspidic acid AB and flavaspidic acid AB. The impact of norflavaspidic acid AB on MRSA cells was examined using untargeted metabolomic analysis and compared to that of other established antibiotics (all treatments normalized to MIC50 at 6 h). This suggested that norflavaspidic acid AB had a distinctive effect which involved targeting bioenergetic transformation, metabolism, and particularly acetyl CoA, in MRSA cells. No cytotoxicity was observed for norflavaspidic acid AB against murine HepG2 cells. This study requires further experimental validation but can have indicated a naturally available compound that could help counter the threat of clinically relevant strains with antibiotic resistance.